Предмет: Алгебра,
автор: cakira2897
Преобразовать выражение в многочлен и упростить выражение
Приложения:
![](https://files.topotvet.com/i/07d/07dfe2c5ff3c661500a1cf670ecd1e09.png)
Ответы
Автор ответа:
1
Ответ:
(3x-1)(3x-1)=9x^2-3x-3x+1=9x^2-6x+1
(2y+3)(2y+3)=4y^2+6y+6y+9=4y^2+12y+9
(x+4y)(x+4y)=x^2+4xy+4xy+16y^2=x^2+8xy+16y^2
(0.5m-2n)(0.5m-2n)=0.25m^2-1n-1n+4n^2=0.25m^2-2n+4n^2
Похожие вопросы
Предмет: Литература,
автор: двымпдлдлв
Предмет: Английский язык,
автор: dimawalik23
Предмет: География,
автор: Катя1505
Предмет: Литература,
автор: Аноним